C Programming Essentials. - Kasi, Dey Nath.; Samir, Bandopadhyay Kumar (2010)
C Programming Essentials is specifically designed t be used at the beginner and intermediate level. The book is organized around language as the tool for design and programming and library functions. It demonstrates key techniques that make C effective and focuses on the fundamental concepts necessary for mastery. An introduction to C99 is also provided.
Summary -- New Terminology Checklist -- Exercises -- Pointers -- Defining a Pointer -- Scalars for Pointers -- Pointer Assignments and Expressions -- Pointer Comparison -- Passing Pointers to Functions -- Pointers and Arrays-Pointer Arithmetic -- Pointers and Two-Dimensional Arrays -- Arrays of Pointers -- Pointers to Pointers -- Pointers to Functions -- Command-Line Arguments -- Other Pointer Issues -- Summary -- New Terminology Checklist -- Exercises -- User-Defined Data Types -- Structures -- Declaring a Structure -- Defining a Structure Variable -- Initializing and Referencing Structure Members -- Nesting of Structures -- Operations on Structures -- Pointers to Structures -- Structures and Functions -- Arrays of Structures -- Self-Referential Structures -- Unions -- Enumerated Data Types -- Typedef -- Bit Fields -- Summary -- New Terminology Checklist -- Exercises -- File Access and Processing -- Introduction -- Opening and Closing a Disc File -- Character Input/Output -- Error-Handling -- Reading and Writing a File in Convenient Chunks -- File Positioning -- Summary -- New Terminology Checklist -- Exercises -- The C Preprocessor -- Macro Substitution -- File Inclusion -- Conditional Compilation -- Additional Directives -- Predefined Preprocessor Identifiers -- ANSI Standard Header files -- Summary -- New Terminology Checklist -- Exercises -- Common Errorsin C -- More on Bitwise Operators in C -- Some Useful Functions from stdlib.h -- Creating Static Library with gcc -- C99-A Brief Introduction -- Practice Problems -- Index -- Back Cover.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2018. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Electronic books